2011
DOI: 10.1089/cyber.2010.0087
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of Personality in Online Social Networks: Self-Reported Facebook-Related Behaviors and Observable Profile Information

Abstract: Despite the enormous popularity of Online Social Networking sites (OSNs; e.g., Facebook and Myspace), little research in psychology has been done on them. Two studies examining how personality is reflected in OSNs revealed several connections between the Big Five personality traits and self-reported Facebook-related behaviors and observable profile information. For example, extraversion predicted not only frequency of Facebook usage (Study 1), but also engagement in the site, with extraverts (vs. introverts) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
327
2
21

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(422 citation statements)
references
References 31 publications
40
327
2
21
Order By: Relevance
“…Indeed, many individuals present an online self more or less consistent with their offline self. 8,9 Research has identified numerous variables that relate to online self-presentation experimentation, including loneliness, 10,11 low levels of social support, 10 low self-esteem, 12 and narcissism. 13 Certain types of individuals may be more predisposed to experiment with self-presentation online, perhaps because they wish to compensate for certain shortcomings or because they are especially motivated to garner desirable impressions.…”
mentioning
confidence: 99%
“…Indeed, many individuals present an online self more or less consistent with their offline self. 8,9 Research has identified numerous variables that relate to online self-presentation experimentation, including loneliness, 10,11 low levels of social support, 10 low self-esteem, 12 and narcissism. 13 Certain types of individuals may be more predisposed to experiment with self-presentation online, perhaps because they wish to compensate for certain shortcomings or because they are especially motivated to garner desirable impressions.…”
mentioning
confidence: 99%
“…There was no statistically significant difference found among the four age groups: F (3, 203) = 1.46, p = . 23. This indicates that the participants' social behavior on Facebook is the same regardless of their age differences.…”
Section: Differences Based On Gender and Agementioning
confidence: 86%
“…These findings were corroborated by other studies [43], which found that users of OSNs maintain or consolidate relationships that are already existing offline rather than make unfamiliar new relationships. Gosling et al [23] agreed that user behavior in online social networks is a reflection of one's social reality in the real world. However, they pointed out that the context of use determines the kind of traits manifested; some traits are more often manifested in some contexts than in others.…”
Section: Computer-mediated Social Lifementioning
confidence: 99%
“…Extroversive adolescents may not prefer sharing photos since they may not consider it as a social activity. Gosling et al (2011) have determined a positive relationship between the number of photos shared and added and the scores of openness for improvement. In this study, no relationship was determined between sharing photos in social media and openness for improvement among the adolescent population.…”
Section: Discussion and Interpretation On If There Is Significant Difmentioning
confidence: 99%